Gold nanoparticle arrays organized in mixed patterns through directed self-assembly of ultrathin block copolymer films on topographic substrates. (6th April 2022) - Eren, Noga; Burg, Ofer; Michman, Elisheva; Popov, Inna; Shenhar, Roy
Abstract: Controlling complexity in assemblies of metal and semiconductor nanoparticles has the potential to expand the utilization of photonic devices into wavelength regimes that are currently inaccessible. Here we show that casting ultrathin films of asymmetric block copolymers on topographically defined substrates affords four types of mixed patterns through fine control of film thickness. Analysis of top-view and cross-sectional images revealed different morphological behavior of the film in the trench and on the plateau, which was explained by the difference in the type of boundary imposed by each topographic feature. Exposed domains were chemically modified and selectively decorated with gold nanoparticles, giving rise to nanoparticle superstructures with mixed patterns in a controlled fashion. We envisage utilization of such hierarchical superstructures as plasmon waveguides and metasurfaces. Graphical abstract: Image 1 Highlights: Casting block copolymer films on topographic substrates leads to mixed patterns. Films in the trenches and on the plateaus behave differently. Plateaus feature soft boundaries; trenches feature hard (impenetrable) boundaries. The morphologies in the trench and on the plateau interact with each other. Our approach provides a simple way to organize nanoparticles into mixed patterns.